Digitalisasi Dakwah dan Matinya Kepakaran - Badriyah, Muawanatul; Hasanah, Amalia (TSAQOFAH, 2025)
This paper discusses the impact of the digitalization of da'wah on the authority of ulama and religious scholars in conveying Islamic teachings to the public. The aim of this study is to identify the factors contributing to the decline in scholarly authority in the era of digital da'wah and to analyze its effects on public understanding of Islamic teachings. Additionally, the research seeks to formulate implementable solutions to preserve the credibility and authority of ulama amid the rise of technology-based da'wah. The method used is field research, involving the direct collection of primary and secondary data from research subjects. The findings reveal that digital da'wah presents new challenges to religious authority, where anyone can share religious views without adequate scholarly grounding, blurring the line between academic authority and personal opinion. To maintain the authority of ulama in the face of overwhelming digital information flows, strategic steps are needed, such as strengthening digital literacy among ulama, active collaboration with digital platforms, and the development of credible official da'wah channels. Additionally, government regulation, increased public religious literacy, and the use of fact-checking technology are crucial to countering the spread of inaccurate religious information. The conclusion of this study affirms that maintaining the authority of ulama in the digital era requires a synergy of scholarship, technology, and policies that are responsive to contemporary dynamics.